Sustained censorship in GB (2026-05) (United Kingdom) - Voidly (2026)
CRITICAL severity censorship detected in United Kingdom. Confidence: 69%. Data sourced from OONI.
Censorship Incident ID: GB-2026-0040
Keywords: censorship; GB; censorship; critical